International bibliography of the social sciences. - Bibliographie internationale des sciences sociales. Prep. by the International Committee for Social Sciences Documentation (Stevens etc., 1962)
1. 1960, VI: Social and cultural anthropology. 378 p. 2. 1960, IX: Economics. 553 p. 3. 1960, IX: Political science. 334 p. 4. 1960, X: Sociology. 287 p. With index.